2022
DOI: 10.1007/s00170-022-10485-9
|View full text |Cite
|
Sign up to set email alerts
|

Tool life prognostics in CNC turning of AISI 4140 steel using neural network based on computer vision

Abstract: One of the essential requirements for intelligent manufacturing is the low cost and reliable predictions of the tool life during machining. It is crucial to monitor the condition of the cutting tool to achieve cost-effective and high-quality machining. Tool conditioning monitoring (TCM) is essential to determining the remaining useful tool life to assure uninterrupted machining to achieve intelligent manufacturing. The same can be done by direct and indirect tool wear measurement and prediction techniques. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The estimations were validated against SMr2 (valley material portion) values measured with a microscope. Bagga et al [13] employed an artificial neural network (ANN) considering the machining parameters for the turning of AISI 4140 steel and used images captured inside the working area of the carbide tools at specific time intervals. The worn area was obtained by processing the images by filtering, enhancement, thresholding and calculating the number of pixels in the area, and the remaining useful life was determined with two activation functions, sigmoid and rectified linear unit (ReLU), achieving an accuracy of 86.5% and 93.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The estimations were validated against SMr2 (valley material portion) values measured with a microscope. Bagga et al [13] employed an artificial neural network (ANN) considering the machining parameters for the turning of AISI 4140 steel and used images captured inside the working area of the carbide tools at specific time intervals. The worn area was obtained by processing the images by filtering, enhancement, thresholding and calculating the number of pixels in the area, and the remaining useful life was determined with two activation functions, sigmoid and rectified linear unit (ReLU), achieving an accuracy of 86.5% and 93.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several literature reviews have identified the main techniques, tools and trends for processing [21][22][23][24]. Firstly, signals are processed directly in the time domain [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or techniques or transforms are used for their analyses in the frequency [3,5,[18][19][20] or time-frequency [19,20] domains. From here, several techniques are used to obtain features that allow the analysis to be carried out in a better way, such as the use of statistical indicators [3][4][5][6]8,14,[18][19][20], time or time-frequency transforms for direct feature extraction [3][4][5]19,20] and, in some cases, methods for the selection of the most appropriate features or dimensionality reduction such as heuristic techniques [5,6,22], linear discriminant analysis (LDA) [19] or principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A flank wear image with ANN was created and used to create a two-step procedure for predicting the life of a tool. Several researchers have considered using ANN to predict tool wear [22][23][24]. ANFIS models were developed to predict the performance of abrasive water jet machining parameters.…”
Section: Introductionmentioning
confidence: 99%